Transcriptional dynamics of immune, growth and stress related genes in skeletal muscle of the fine flounder (Paralichthys adpersus) during different nutritional statuses. Issue 1 (November 2015) - Valenzuela, Cristián A.; Escobar, Daniela; Perez, Lorena; Zuloaga, Rodrigo; Estrada, Juan Manuel; Mercado, Luis; Valdés, Juan Antonio; Molina, Alfredo
Abstract The effects of stress on immune activity and growth in early vertebrates have not been studied in detail. The present study used fine flounder (Paralichthys adspersus) skeletal muscle as a model to evaluate molecules involved in the stress response, including the glucocorticoid receptors, foxo1/3, and the target genes of these. Additionally, immune markers (il-1β and tnfα) and effector molecules of atrophy (bnip3, caspase-3, and lc3) were assessed. These molecules were analyzed during periods of long-term fasting and refeeding. During fasting, gene expression related to the stress response and atrophy increased; whereas immune markers were down-regulated. During refeeding, atrophy- and stress-related gene expression significantly decreased. In contrast, immune markers were up-regulated. These results provide novel insight on the control of growth in the skeletal muscle of a non-mammalian species under a stressful condition, suggesting that growth, stress, and immune activity in muscle are closely related and coordinated by orchestrated transcriptional dynamics.